Effects of flow separation and shape factor of nanoparticles in heat transfer fluid for convection thorough phase change material (PCM) installed cylinder for energy technology applications - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2021)
In this study, flow separation effects on the performance of PCM embedded thermo-fluid system is numerically analyzed by using the finite element method. In the heat transfer fluid, shape effects of nanoparticles are considered. Spherical, blade, brick and cylindrical shaped alumina nanoparticles are used in water. The numerical work is performed for different values of Reynolds number (between 100 and 300), expansion ratio of the channel (0.35 and 1), nanoparticle volume fraction (between 0 and 2%) and different shape of particles. The PCM material is paraffin wax with spherical shaped capsules of 20 mm in diameter. There is significant impact of channel expansion and flow separation zone on the performance of the system. When the area expansion is introduced in the straight channel, the configuration with the highest Reynolds number resulted in performance degradation due to flow recirculation extended in the PCM region. The charging time for a straight channel is reduced by about 84% when comparison is made with the channel having an expansion ratio of 0.35. The shape factor of the alumina nanoparticles significantly affects the flow recirculations and thermal exchange between the PCM and heat transfer fluid. Among various particles, cylindrical shaped one performs best while 23.8% reduction in charging time is obtained at the highest solid volume fraction when comparison is made with pure water as heat transfer fluid.
Keywords: Particle shape; Phase change material; Backward facing step; Nanofluids; Finite element method